Leptin, its receptor and aromatase expression in deep infiltrating endometriosis - Gonçalves, Helder F. (J Ovarian Res, 2015)
BACKGROUND: The aim of this study was to evaluate the leptin levels in the serum and peritoneal fluid (PF) and the protein expression in three different peritoneal ectopic implants in patients who underwent surgery for deep infiltrating endometriosis. METHODS: All patients had been treated at the Department of Gynecology of the Pedro Ernesto University Hospital, Rio de Janeiro. The study group consisted of 15 patients who underwent surgery for adnexal masses and infertility, while the control group consisted of ten women who underwent surgery for tubal ligation. Peritoneal fluid and samples tissues were collected during surgery. Serum samples were obtained before anesthesia. In this study, the leptin levels in the serum and peritoneal fluid (PF) were evaluated by ELISA. The protein expression of leptin and its receptors (ObR) and aromatase enzyme were evaluated by Western blot analysis of the intestine, uterosacral ligament and vaginal septum in the ectopic implants. The t-test and one-way ANOVA with Holm-Sìdak post-test were used, and p < 0.05 was considered to be statistically significant. RESULTS: Compared to the controls, the serum leptin levels (control = 14.7 ng/mL ± 2.63, endometriosis = 19.2 ng/mL ± 1.84, p < 0.0001) were increased, while in PF, there was no difference (control = 6.68 ng/mL ± 0.43, endometriosis = 7.71 ng/mL ± 0.59, p = 0.18). Comparing women with and without ovarian implants, the leptin levels in both the serum and PF were significantly higher in women without ovarian implants (serum: with ovarian implant = 15.85 ± 1.99; without ovarian implant = 23.14 ± 2.60; ng/mL, p = 0.04; PF: with ovarian implant = 4.28 ± 1.30; without ovarian implant = 11.18 ± 2.98;ng/mL, p = 0.048). The leptin, ObR and aromatase protein expression levels were increased in lesions in the vaginal septum and were decreased in the intestine lesions. CONCLUSION: This study reports several interesting associations between the leptin levels in serum, peritoneal fluid, and tissue samples and the localization of the ectopic endometrium. Although this study does not provide a clear picture of the role of leptin in the development and progression of peritoneal implants, it contributed new data that might be useful to elucidating the enigma that is the role of leptin in endometriosis disease.